2020
DOI: 10.1210/jendso/bvaa081
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Molecular Testing in Sonographically Suspicious Thyroid Nodules

Abstract: Objective Molecular testing can refine the diagnosis for the 20% of thyroid fine needle aspiration biopsies that have indeterminate cytology. We assessed the diagnostic accuracy of molecular testing based on ultrasound risk classification. Methods This retrospective cohort study analyzed all thyroid nodules with indeterminate cytology at an academic U.S. medical center (2012-2016). All indeterminate nodules underwent reflexiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…Regarding molecular panels, 25 studies evaluated the diagnostic performance of the Afirma GEC ( 8 , 16 , 17 , 40 , 47 54 , 56 58 , 61 , 63 , 64 , 66 70 , 72 , 76 , 77 ), and four articles reported the Afirma GSC ( 16 , 17 , 57 , 70 ). Thyroseq versions 2 and 3 were found in nine ( 11 , 15 , 58 , 59 , 61 , 62 , 71 , 73 , 75 ) and four papers ( 14 , 55 , 59 , 65 ), respectively, while ThyraMIR/ThyGenX ( 23 , 67 , 68 ) and ResettaGX Reveal ( 61 , 67 , 68 ) were explored in three studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding molecular panels, 25 studies evaluated the diagnostic performance of the Afirma GEC ( 8 , 16 , 17 , 40 , 47 54 , 56 58 , 61 , 63 , 64 , 66 70 , 72 , 76 , 77 ), and four articles reported the Afirma GSC ( 16 , 17 , 57 , 70 ). Thyroseq versions 2 and 3 were found in nine ( 11 , 15 , 58 , 59 , 61 , 62 , 71 , 73 , 75 ) and four papers ( 14 , 55 , 59 , 65 ), respectively, while ThyraMIR/ThyGenX ( 23 , 67 , 68 ) and ResettaGX Reveal ( 61 , 67 , 68 ) were explored in three studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The panels with the fewest assessments were ThyraMIR/ThyGeNEXT and miRInform ( 23 , 74 ). The majority of the studies (n = 32) evaluate a single molecular panel, of which 18 articles reported Afirma GEC alone ( 8 , 40 , 47 54 , 56 , 63 , 64 , 66 , 69 , 72 , 76 , 77 ), nine papers assessed second or third version of Thyroseq NGS ( 11 , 14 , 15 , 55 , 62 , 65 , 71 , 73 , 75 ) and lastly, ThyraMIR/ThyGeNEXT, ThyraMIR/ThyGenX, miRInform and RosettaGX Reveal were each approached in a study ( 21 , 23 , 60 , 74 ). Among the nine studies that measured up more that two molecular panels, four paper compared Afirma GEC and GSC ( 16 , 17 , 57 , 70 ), two manuscripts reported a comparison between Afirma GEC and Thyroseq v2 ( 58 , 61 ), two papers investigated the diagnostic performance of Afirma GEC, RosettaGX and Interpace MPT ( 67 , 68 ) and Jug et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations